THE INFLUENCE OF TASTE AND PERCEPTION OF QUALITY ON PURCHASING DECISIONS THROUGH PURCHASE INTENTION AS AN INTERVENING VARIABLE (CASE STUDY OF MIMI RESTAURANT CUSTOMERS, TEBING TINGGI CITY) - Rumiris Siahaan; Rizki Wulanita; Rahmawati Purba (PT. Radja Intercontinental Publishing, 2024)
This research aims to find out how taste and perceived quality influence purchasing decisions through purchase intention as an intervening variable (case study of customers at Mimi Restaurant, Tebing Tinggi City). The population in this research is Mimi Restaurant customers, with an average of 1520 customers per month. In determining the sample size, the Slovin formula was used, namely 75 respondents. The regression analysis method used is multiple linear regression and to test the hypothesis the t test and path analysis test are used. The research data were analyzed or processed using the SPSS version 25 program. From the results of this research it can be concluded that taste influences the purchase interest variable, perceived quality influences the purchase interest variable, taste influences the purchase decision variable, quality perception influences the purchase decision variable. purchase decision, purchase interest has no effect on the purchase decision variable, purchase interest cannot mediate between the taste variable on the purchase decision, purchase interest cannot mediate between the quality perception variable on the purchase decision.